Imaging the Postoperative Elbow - Deely, Diane M.; Morrison, William B. (Seminars in Musculoskeletal Radiology, 2021)
Evaluation of postoperative images of any joint can be a daunting task, and the elbow is no exception. Patients may be imaged with a complication of the repair, or the postoperative changes may be incidentally observed as the patient is imaged for other reasons. We divide the postoperative elbow into soft tissue procedures (covering ligament and tendon repairs, as well as compartmental release and nerve transposition), joint-related procedures (osteochondral lesion treatment, ostectomy, and joint replacement), and bone procedures (fracture fixation). We summarize the procedures and their indications, show normal imaging appearances, and finally cover common complications.
Keywords: elbow; postoperative; repair; surgical; magnetic resonance imaging